Systematics of Podocoma (Asteraceae: Astereae): a generic reassessment - Sancho, Gisela (2010)
Podocoma is a southern South American genus of perennial herbs with short-radiate capitula with two- to four-seriate ray florets and a two- to three-seriate pappus of scabridulous setae. The ray florets have corollas with narrow limbs. The rostrate cypsela of Podocoma is one of the most distinct features of the genus. Podocoma, with many of the endemic southern South American genera of Astereae, is included in subtribe Podocominae. Podocoma traditionally contained seven mainly Brazilian species (P. asperrima, P. bellidifolia, P. blanchetiana, P. hieracifolia, P. hirsuta, P. regnellii and. P. spegazzinii), and its expansion to include two species of Conyza (C. notobellidiastrum and C. rivularis) was, perhaps, the most significant recent change in the generic concept of Podocoma. However, recent molecular- and morphology-based phylogenetic analyses do not support the inclusion of these two species in Podocoma. Morphological and anatomical studies were carried out in order to clarify the taxonomy of Podocoma and to delimit the genus and its species. On the basis of the results of these morphological and anatomical studies, and those from molecular- and morphology-based phylogenetic analyses, P. notobellidiastrum and P. rivularis are excluded from Podocoma and transferred to a new genus that is currently under description. Moreover, P. regnellii and P. asperrima are placed in synonymy with P. hirsuta and P. spegazzinii, respectively. Three species, P. bellidifolia, P. blanchetiana and P. hieracifolia, are recognized here as a complex of closely related species from a morphological point of view; however, they are treated separately.